To solve the system of equations:
- \( y = x^2 + 10 \)
- \( y = -7x - 2 \)
we will use the elimination method by setting the two equations equal to each other.
First, set the right-hand sides equal:
\[ x^2 + 10 = -7x - 2 \]
Now, let's rearrange this equation:
\[ x^2 + 7x + 12 = 0 \]
Next, we can factor this quadratic equation:
\[ (x + 3)(x + 4) = 0 \]
Setting each factor equal to zero gives us the solutions for \( x \):
- \( x + 3 = 0 \) → \( x = -3 \)
- \( x + 4 = 0 \) → \( x = -4 \)
Now we can find the corresponding \( y \) values by substituting these \( x \) values back into either equation. We'll use \( y = -7x - 2 \).
For \( x = -3 \):
\[ y = -7(-3) - 2 = 21 - 2 = 19 \] So one solution is \( (-3, 19) \).
For \( x = -4 \):
\[ y = -7(-4) - 2 = 28 - 2 = 26 \] The other solution is \( (-4, 26) \).
Thus the solutions to the system are \( (-3, 19) \) and \( (-4, 26) \).
The correct response is: \[ (-3, 19) \text{ and } (-4, 26) \]